9(x-a)=y

Simple and best practice solution for 9(x-a)=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-a)=y equation:


Simplifying
9(x + -1a) = y

Reorder the terms:
9(-1a + x) = y
(-1a * 9 + x * 9) = y
(-9a + 9x) = y

Solving
-9a + 9x = y

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-9a + 9x + -9x = -9x + y

Combine like terms: 9x + -9x = 0
-9a + 0 = -9x + y
-9a = -9x + y

Divide each side by '-9'.
a = x + -0.1111111111y

Simplifying
a = x + -0.1111111111y

See similar equations:

| 3x+6x^2=500 | | 4x+6x^2=500 | | r=(b+a)m | | 121=i | | ((x-2)^(2)(x^(2)-1))/((x-1)^(2)(x^(2)-4)) | | -(5/8)a-20=-10 | | 3(x+8)=y | | 150x-(3100+5x+.1x^2)=0 | | x=1*0.75 | | (2x+1)(1+x)=2(1-x)+6 | | 7+-5=6+-2 | | 6(x+4)+4=-14 | | 3h=21/2 | | 4x^2+32x=-65 | | 8.4=-logx | | 495.4/713.36 | | 6.4=2p | | m-22/4-4m-27/5=1 | | x^2+16-16x+x^2=4-4x+x^2 | | 3b/2b | | a+16=3a-3+a | | x/-15-160 | | 7.8-11r=-6.2-r | | (x-2)(x+1)+(x-2)(x+2)=0 | | 5/6x=26/36 | | 6/4=m/9 | | 2(3x+18)=66 | | (4+z)(2z-3)=0 | | -x-6*2=24 | | (2m)^3/5 | | 2/5b=4 | | 3x+6-5(x+1)=7x+8 |

Equations solver categories